Nematicidal effects of extracts of garlic, grape pomace and olive mill waste, on Meloidogyne incognita, on grapevine cv Chardonnay - Martinotti, Marcelo Diego; Castellanos, Sergio Juan; González, Roxana; Camargo, Alejandra; Fanzone, Martin (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2016)
Meloidogyne incognita, significantly affects the grapevines in Argentina. Currently there are few tools available to control this pest. The objective of this work was to compare the nematicidal effects of aqueous extracts of garlic bulbils, immature compost of olive mill waste, immature compost of fresh grape pomace and immature compost of spent grape pomace on the galling index (IA), the rate of reproduction of the eggs and juveniles J2 (IR) and the final population of M. incognita females (H) in grapevines, cv Chardonnay. The experiments were performed with potted plants of grapevines cv Chardonnay, in greenhouse conditions. The only treatment that showed statistically differences compared to the control, was the extract of garlic bulblets; while the extracts of immature compost of olive mill waste, immature compost of fresh grape pomace and immature compost of spent grape pomace, did not affect the evaluated parameters. The extract of garlic bulblets decreased by 73% the IA, 80% the IR and 94% H, therefore the development from this material of an organic nematicide with low environmental impact could be expected.